yrivers36
  • yrivers36
Please help me with this system. I'm not getting the y or z. -x+2y+z=2 3x+y+z=12 x-y-2z=-1
Mathematics
schrodinger
  • schrodinger
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
(3,2,1)
yrivers36
  • yrivers36
Can u explain it to me please?
anonymous
  • anonymous
are you supposed to use elimation?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

yrivers36
  • yrivers36
Either elimination or substitution
anonymous
  • anonymous
ok we can eleminate z first
anonymous
  • anonymous
satellite, i wasnt done, i still needed helpp :/
anonymous
  • anonymous
\[-x+2y+z=2\] \[ 3x+y+z=12\]
anonymous
  • anonymous
subtract and get \[-4x+y=-10\] as one equation with no z in it
anonymous
  • anonymous
now \[3x+y+z=12\] \[ x-y-2z=-1\] multiply first equation by 2 get \[6x+2y+2z=24\] \[x-y-2z=-1\] add and get \[7x+y=23\]
anonymous
  • anonymous
now we have \[-4x+y=-10\] and \[7x+y=23\] so solve
anonymous
  • anonymous
subtact second one from first and get \[-11x=-33\] making \[x=3\] now substitute back to find y, and then z
yrivers36
  • yrivers36
Where did the y go in the -4x+y=-10 and 7x+y=23
anonymous
  • anonymous
i subtracted the second equation from the first
yrivers36
  • yrivers36
oh you multiplied by -1
anonymous
  • anonymous
or if you prefer, multiply the second by -1 and then add,
anonymous
  • anonymous
yes exactly it is the same thing
yrivers36
  • yrivers36
ok I got it finally thank you so much for your help
anonymous
  • anonymous
\[-4x+y=-10\] \[-7x-y=-23\] \[-11x=-33\] etc yw

Looking for something else?

Not the answer you are looking for? Search for more explanations.